Knowledge and Attitudes about Precautionary Measures of COVID-19 among Undergraduate Students: A Comparative Study - Halmat Authman Rasheed (Hawler Medical University, 2022)
Background and objective: The pandemic caused by novel Coronavirus Disease 2019 (COVID-19) is an infectious respiratory illness caused by a new coronavirus that first appeared in China at the end of December 2019 and quickly spread worldwide. The aims of this study are to assess undergraduate students' knowledge and attitudes of the precautionary measures toward COVID-19. Methods: A descriptive comparative study design was used from 2nd January to 1st March 2022. A purposive sampling technique was used to collect the data. All students (240 students) in second grade from the nursing department and the English department at Gasha Technical Institute, Kurdistan Region/Iraq, were recruited and completed a self-reported questionnaire. Result: Around 70% of nursing students and 69% of students in the English department were males, and most students in both fields were aged between 18 and 22 years old. A total of 83.3 % of students in nursing and 77.5% of students in the English department were single. However, the rate of married students (21.7%) was higher in the English department. More than half of the nursing students (63.3%) showed good knowledge, 31.7% showed medium knowledge, and 5.0% showed poor knowledge. Nursing students' good attitude was 15.8%. In contrast, 30.0% of students in the English department had good knowledge, 50.8% had medium knowledge, and 19.2% had poor knowledge. Good attitude of students in the English department was 5%. Conclusion: Overall, a higher level of knowledge was observed in nursing students than students in the English department. Also, positive attitude toward COVID-19 was higher among nursing students.